Assessment of psychosocial care in alcohol and other drugs from the perspective of patients (Research, Society and Development, 2021)
The processes of assessment of health services have used the reports of the users as element in the composition of parameters of evaluation of results. This study aimed to evaluate patients' satisfaction and their perception of changes resulting from the care provided by a psychosocial care service in alcohol and drugs. The descriptive, cross-sectional and qualitative study employed the theoretical-methodological reference of the Adapted Fourth Generation Assessment, collecting data through observation, individual interviews with the Hermeneutic-Dialectic Circle and group interviews. The users expressed that they feel satisfied with the service offered by the service, emphasizing the quality of the reception. Regarding to the perception of change, the participants recognized positive changes in their lives as treatment outcomes, highlighting effects on the use of psychoactive substances, the organization of their lives and their family ties.